2015
DOI: 10.1124/jpet.115.229997
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Functions of B-Type Natriuretic Peptide, Gastrin-Releasing Peptide, and Their Cognate Receptors for Regulating Itch in Mice

Abstract: B-type natriuretic peptide (BNP)-natriuretic peptide receptor A (NPRA) and gastrin-releasing peptide (GRP)-GRP receptor (GRPR) systems contribute to spinal processing of itch. However, pharmacological and anatomic evidence of these two spinal ligandreceptor systems are still not clear. The aim of this study was to determine the spinal functions of BNP-NPRA and GRP-GRPR systems for regulating scratching activities in mice by using pharmacological and immunohistochemical approaches. Our results showed that intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…4A) [32; 39; 40]. Scratching behavior resulting from the intrathecal administration of Nppb is blocked by pretreatment with a Grpr antagonist [19]. Wild-type and Nppb −/− mice, but not Grpr −/− mice, exhibit scratching behavior in response to the intrathecal administration of GRP [32; 39].…”
Section: Resultsmentioning
confidence: 99%
“…4A) [32; 39; 40]. Scratching behavior resulting from the intrathecal administration of Nppb is blocked by pretreatment with a Grpr antagonist [19]. Wild-type and Nppb −/− mice, but not Grpr −/− mice, exhibit scratching behavior in response to the intrathecal administration of GRP [32; 39].…”
Section: Resultsmentioning
confidence: 99%
“…They also demonstrated BNP transmitted itch signals to NPRA expressed primarily in lamina I to contribute to spinal processing of itch (Mishra & Hoon, ). The BNP released from peripheral sensory neurons stimulates its receptor in NPRA + ‐spinal cord neurons to release GRP in the spinal cord to activate canonical GRP receptor ( Grpr ) + ‐neurons in order to transmit itch signal to the brain (Hoon, ; Kiguchi et al, ). In addition, Nppb −/− mice, but not Grpr −/− mice, exhibit scratching behaviour upon intrathecal injection of GRP (Mishra & Hoon, ; Sun & Chen, ).…”
Section: Role Of Bnp In Itch Transmission In the Spinal Cordmentioning
confidence: 99%
“…Initially, Kiguchi et al observed that the onset and magnitude of intrathecal BNP‐induced scratching are slower and smaller than that induced by intrathecal GRP (Kiguchi et al, ), thus raising the hypothesis that BNP initiates itch indirectly through activation of a GRP pathway. They showed that intrathecal administration of BNP antagonist A71915 in mice had no effect on intrathecal GRP‐induced scratching, whereas the GRP antagonist RC‐3095 inhibited BNP‐induced scratching (Kiguchi et al, ), confirming that the BNP‐NPRA system may act upstream of GRP‐GRPR to regulate itch in the mouse spinal cord (Kiguchi et al, ). In their study, A71915 also had little effect on peripherally elicited scratching upon intradermal injection of ET‐1, thromboxane A 2 analogue, BAM8‐22 (activator of MrgprC11), and SLIGRL (a PAR2 agonist) in mice, thus concluding that there was a minimal role for the spinal BNP‐NPRA system in regulating peripheral itch (Kiguchi et al, ).…”
Section: Potential Therapeutic Targets For Bnp Signalling In Itchmentioning
confidence: 99%
See 2 more Smart Citations